"Psycho-educative intervention for students with learning difficulties-A regional study" - Hida, Manolita; Mustafaraj, Elona; Kaziu, Besiana (IJRDO- Journal of Educational Research, 2017)
Various studies indicate that using intervention strategies in children with learning difficultiesgives positive results in improving the issues outlined by them.However there are gaps between strategies and what teachers use in classrooms.